2020
DOI: 10.1007/s11098-020-01526-8
|View full text |Cite
|
Sign up to set email alerts
|

Aphantasia, imagination and dreaming

Abstract: Aphantasia is a recently discovered disorder characterised by the total incapacity to generate visual forms of mental imagery. This paper proposes that aphantasia raises important theoretical concerns for the ongoing debate in the philosophy and science of consciousness over the nature of dreams. Recent studies of aphantasia and its neurobehavioral correlates reveal that the majority of aphantasics, whilst unable to produce visual imagery while awake, nevertheless retain the capacity to experience rich visual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 58 publications
3
8
0
Order By: Relevance
“…Concerning the second point, the current study is, to our knowledge, the first to illustrate that aphantasia also encompasses an inability to engage in implicit motor simulations. This result extends recent investigations demonstrating the deterioration of implicit simulations during mental rotation (Pounder et al, 2022; Zeman et al, 2010; Zhao et al, 2022; but Milton et al, 2021) and involuntary simulations during night-time dreams (Dawes et al, 2020; Zeman et al, 2015, 2010; see review: Whiteley, 2020). As already described for motor imagery, we observed that, relative to rest, action observation increased corticospinal excitability in phantasics but not aphantasics.…”
Section: Discussionsupporting
confidence: 89%
“…Concerning the second point, the current study is, to our knowledge, the first to illustrate that aphantasia also encompasses an inability to engage in implicit motor simulations. This result extends recent investigations demonstrating the deterioration of implicit simulations during mental rotation (Pounder et al, 2022; Zeman et al, 2010; Zhao et al, 2022; but Milton et al, 2021) and involuntary simulations during night-time dreams (Dawes et al, 2020; Zeman et al, 2015, 2010; see review: Whiteley, 2020). As already described for motor imagery, we observed that, relative to rest, action observation increased corticospinal excitability in phantasics but not aphantasics.…”
Section: Discussionsupporting
confidence: 89%
“…Thus, current data plausibly underestimates the cases of non-visual imagery impairments. 4 For aphantasia and dreaming, see Whiteley (2020). and night dreams; as well as the subjective experiences rating scale comprising of 39 questions assessing participants' night dreams.…”
Section: Involuntary Imagerymentioning
confidence: 99%
“…On the face of it, that is a significant benefit that the volitional account has over the metacognitive one. Similar claims have been made about the capacity of volitional account to explain how it is that aphantasics report dreams, since dreaming is an imagery-based process that mostly occurs involuntarily (Whiteley, 2021).…”
Section: Defining the Imagery Deficitmentioning
confidence: 63%